Estudo da afetividade de moradores do centro de Fortaleza-CE frente ao Plano Habitacional para Reabilitação da Área Central de Fortaleza-CE - Bandeira, Brennand de Sousa (2012)
This research proposes to investigate affective relationships among the residents of Fortaleza’s core. The study is guided by an interdisciplinary collaboration between the environmental diagnosis of urban space and the application of instruments generators of Affective Maps (BOMFIM, 2010), a methodology of affections apprehension originated from the Environmental Psychology and Social Psychology. The environmental diagnosis of the historic core was designed adopting as parameter elements highway system and the use and occupation of soil, listed in Law No. 7987 of December 23, 1996 (Use and Soil Occupation’s Law). Referenced in the sociourban situation of housing use, our analysis identified 04 (four) regions with relatively distinct environmental characteristics among themselves. The sample was composed by 100 subjects of both genders (residents of the Historic Core) chosen for convenience. We apply the tools generators of Affective Maps and complement the survey with a questionnaire containing 15 closed questions about the living conditions of the core. The methodology of the Affective Maps’ generator tool enabled us to apprehend the feelings and emotions of the subjects from the following affective images: Belonging, Contrast, Destruction, Agreeableness, Attraction and Insecurity. In additional analysis of Affective Maps, statistics worked out by ANOVA, took into account each image and sectors already commented. The results indicated significant differences among the levels of Agreeableness, Belonging, Destruction and Attraction in relation to sectors previously diagnosed. The results obtained in the study were relevant for the understanding of emotions and meanings established by the subjects in their relationship with the neighborhood. Those data, if associated with the process of popular participation proposed by the plans may be important findings for the projection of urban and social policies more consistent with aspects experienced by the target audience of the plans.